2014
DOI: 10.1108/ijm-06-2013-0130
|View full text |Cite
|
Sign up to set email alerts
|

Occupational mobility over the business cycle

Abstract: Purpose -The purpose of this paper is to examine how occupational mobility varies over the business cycle and how selected factors contribute to occupational mobility in different stages of the business cycle. Design/methodology/approach -Using annual micro data from the Estonian Labour Force Survey (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) and implementing probit models with interaction terms, the paper investigates occupational mobility as a change of occupation in two successive years dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…22. This is not in contrast with the results obtained in Ghignoni and Verashchagina (2014) who, using a different approach, found significant AWE only for low-educated women in the South of Italy, characterised by the lowest participation rate. It is also supportive to the findings by Roosaar et al (2014) who claim that occupational mobility is lower during the recession stage.…”
Section: Notessupporting
confidence: 90%
“…22. This is not in contrast with the results obtained in Ghignoni and Verashchagina (2014) who, using a different approach, found significant AWE only for low-educated women in the South of Italy, characterised by the lowest participation rate. It is also supportive to the findings by Roosaar et al (2014) who claim that occupational mobility is lower during the recession stage.…”
Section: Notessupporting
confidence: 90%
“…Research in economics has also shown that it is easier for employees to have a career when they have completed higher education (Becker, 1993in: Roosaar et al, 2014Hennekam, 2015). The conventional economic view is that education boosts an individual's productivity and therefore increases his market value (Arrow, 1973, p. 193).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Venhorst et al (2011) find that job migration of Dutch university graduates is less common during boom periods than during recessionary 1 3 periods. Moreover, Roosaar et al (2014) investigate occupational mobility and its determinants among Estonian workers over the business cycle. They find that demographic characteristics influence job mobility between 2001 and 2003, a period of recovery from a recession.…”
Section: The Macro-economic Contextmentioning
confidence: 99%